The Association of Race/Ethnicity and Patch Test Results: North American Contact Dermatitis Group, 1998–2006. Issue 5 (September 2016) - Deleo, Vincent Anthony; Alexis, Andrew; Warshaw, Erin M.; Sasseville, Denis; Maibach, Howard I.; DeKoven, Joel; Zug, Kathryn A.; Belsito, Donald V.; Fowler, Joseph F.; Marks, James G.; Mathias, C.G. Toby; Pratt, Melanie D.; et al.
Abstract : Background: The North American Contact Dermatitis Group patch tests patients with suspected allergic contact dermatitis (ACD) to a broad series of screening allergens and publishes periodic reports. We have previously reported on the association of race and ethnicity with the rates of positive responses to standard patch test allergens. This report extends those observations. Objective: The aim of the study was to report the North American Contact Dermatitis Group patch testing results from January 1, 1998, to December 31, 2006, comparing the frequency of positive reactions between white and black subjects. Methods and Materials: Standardized patch testing with 45 allergens was used at 13 centers in North America. χ 2 analysis of results in black subjects as compared with whites was examined. Results: A total of 19, 457 patients were tested; 92.9% (17, 803) were white and 7.1% (1, 360) were black. The final diagnoses of ACD (whites, 45.9%; blacks, 43.6%) and irritant contact dermatitis (13.0%/13.3%) were similar in the 2 groups. The diagnosis of atopic dermatitis was less common in the white patients (8.9%) as compared with the black patients (13.3%). Positive patch test reactions rates were similar for most allergens. However, statistically, blacks reacted more frequently to p -phenylenediamine (7.0% vs 4.4%, P < 0.001), bacitracin (11.6% vs 8.3%, P = 0.0004), as well as specific rubber accelerators mercaptobenzothiazole (2.7% vs 1.8%), thiuram (6.2% vs 4.3%), and mercapto mix (1.9% vs 0.8%, P < 0.001). Whites had an increase in positive reactions to fragrances (12.12% vs 6.77%, P < 0.0001), formaldehyde (9.25% vs 5.45%, P < 0.0001), and some formaldehyde releaser preservatives used in personal care products and textile resins (9.80% vs 6.18%, P < 0.0001). Conclusions: There were statistically different rates of positive patch test reactions to specific allergens between black and white patients suspected of having ACD. The etiology of these differences is unclear but probably relates to culturally determined exposure patterns rather than genetic differences.